PERANCANGAN USER INTERFACE PADA START-UP GADGET STORE MENGGUNAKAN METODE USER CENTERED DESIGN - Syujak, Ahmad Rois; Friadi, John; Royyana, Fia (STMIK BINA PATRIA, 2025)
The development of digital technology has driven the rapid growth of various startups in Indonesia, particularly in e-commerce. One sector experiencing significant growth is the online sale of electronic devices and gadgets. Consumers now prefer online transactions due to their perceived convenience, efficiency, and flexibility. However, amidst intense competition between e-commerce platforms, user experience has become a key factor in the success of an application or website. This study aims to identify user needs and preferences when interacting with the Gadget Store application, design a user interface prototype that applies User-Centered Design principles, and evaluate the level of usability and user satisfaction with the resulting interface design. The system development method used was User-Centered Design, while the problem analysis used SWOT and the feasibility study used TELOS. The UI design testing process used 10 Usability Heuristic indicators, with a test result of 87%. This proves that the digital startup designed meets user needs. The Gadget Store startup is expected to provide users with convenience in searching for iPhone information, including ease of transactions. Keywords: digital start-up, Gadget Store, User Centered Design, TELOS, Usability Heuristic